Unveiling the Hidden Meanings Behind the Karembong Beureum Illustration: A Study of Visual Communication Semiotics in the Work of Ayi R. Sacadipura - Yudi Rudiyansyah (Universitas Pasundan, 2025)
Illustrations serve as a powerful form of visual communication, conveying messages and meanings that transcend words. This study delves into the visual expression style of Ayi R. Sacadipura, specifically focusing on the illustration titled